Kemampuan Literasi Numerasi Ditinjau dari gaya Kognitif Reflektif-Impulsif - Rahmawati Patta; Awaluddin Muin; Mujahidah Mujahidah; Yonthan Pasinggi (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2021)
The purpose of this study was to determine how the level of numeracy literacy skills of students based on cognitive style, namely reflective-impulsive. The method used in this study was a quantitative research with a survey method. The object of the study or population was the 2018 PGSD Bone student class using the MFFT test to see cognitive style and written test related to numeracy literacy skills. The result of the research and discussion showed that the numeracy literacy ability of students was still not maximal, namely 34.7%. Judging from the cognitive style, 55% entered into reflective cognitive style and 22.08% entered an impulsive style. The reflective cognitive style in solving the questions takes a long time, but the results obtained to be correct or accurate, while the impulsive cognitive style is said to rush in answering and tend to be wrong. Another finding is that there are reflective cognitive style with a long time used but the answers are also many wrong and about 10% impulsive style answers correct in a short time. To improve numeracy literacy skills, a learning strategy or model is needed in accordance with the characteristics of students to develop creative, critical, high-order thinking by integrating 21st century